Meningkatkan Keterampilan Berbahasa Indonesia Melalui Metode Demonstrasi - Roida Sidauruk (JURNAL GLOBAL EDUKASI, 2021)
Abstract: This classroom action research aims to improve Indonesian language skills through the method of demonstration of speech material with clear intonation and volume of voice for grade IX students of SMPN 1 Sei Kepayang district Asahan academic year 2018/2019. This classroom action research was conducted in 2 cycles. The subjects of this study were students of class IX SMPN 1 Sei Kepayang district. Asahan, data were collected through observation, interviews, tests, and study documentation. The results of the learning process before the research improve Indonesian language skills through the Demonstration method of the subject matter of speech with clear intonation and volume of voice reaching an average value of 49.81, after being motivated, research was carried out through cycle I and cycle II of reflection and the recommended average value reached 85.94 . The results of classical learning completeness in cycle I reached an average value of 76.91% after cycle I and cycle II, reflection and classical learning completeness recommendations reached 85.94%. Keywords: demonstration; intonation; speech  Abstrak: Penelitian tindakan kelas ini bertujuan untuk meningkatkan keterampilan berbahasa Indonesiamelalui metode Demonstrasi materi berpidato dengan intonasi dan volume suara yang jelas siswa kelas IX SMPN 1 Sei Kepayang kab. Asahan TP. 2018/2019. Penelitian tindakan kelas ini dilaksanakan dalam 2 siklus. Subjek penelitian ini adalah siswa kelas IX SMPN 1 Sei Kepayang kab. Asahan, data dikumpulkan melalui observasi, wawancara, test, dan study dokumentasi. Hasil proses belajar sebelum penelitian meningkatkan kete-rampilan berbahasa Indonesia melalui metode Demonstrasi materi pokok berpidato dengan intonasi dan volume suara yang jelas mencapai nilai rata-rata 49.81, setelah termotivasi dilakukan penelitian melalui siklus I dan siklus II refleksi dan rekomendasi nilai rata-rata mencapai 85.94. Hasil ketuntasan belajar klasikal pada siklus I mencapai nilai rata-rata 76.91% setelah siklus I dan siklus II, refleksi dan rekomendasi ketuntasan belajar klasikal mencapai 85.94%.           Kata Kunci: demonstrasi; intonasi; pidato